2006
DOI: 10.1021/jf051853j
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of Nonpolar Constituents from Different Parts of Kava Plant (Piper methysticum)

Abstract: Kava (Piper methysticum), a perennial shrub native to the South Pacific islands, has been used to relieve anxiety. Recently, several cases of severe hepatotoxicity have been reported from the consumption of dietary supplements containing kava. It is unclear whether the kava constituents, kavalactones, are responsible for the associated hepatotoxicity. To investigate the key components responsible for the liver toxicity, bioassay-guided fractionation was carried out in this study. Kava roots, leaves, and stem p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 10 publications
6
49
0
2
Order By: Relevance
“…Jhoo et al (62) investigated in vitro cytotoxicity of kavalactones-containing fractions from different parts of kava plant (Piper methysticum) to HepG2. It was found that the hexane fraction of the root exhibited stronger cytotoxic effects than the fractions of root extracted by other solvents or extracts from the leaves and stem peelings of kava.…”
Section: Short-term Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jhoo et al (62) investigated in vitro cytotoxicity of kavalactones-containing fractions from different parts of kava plant (Piper methysticum) to HepG2. It was found that the hexane fraction of the root exhibited stronger cytotoxic effects than the fractions of root extracted by other solvents or extracts from the leaves and stem peelings of kava.…”
Section: Short-term Testsmentioning
confidence: 99%
“…Jhoo et al (62) reported that kava enhanced the hypnotic effect of alcohol in mice. Liu et al (85) determined that alteration of cytochrome P450 expression level can affect the preneoplastic changes in the early stage of hepatocarcinogenesis in Sprague-Dawley rats.…”
Section: Alteration Of Cytochrome P450 Metabolizing Isozymes-it Has Bmentioning
confidence: 99%
“…Com relação a citotoxicidade, Jhoo et al (2006) encontraram nas frações aquosas da raiz de 79,6 a 102% de viabilidade celular, sendo o composto responsável pela citotoxicidade identificado, a flavokavaina B. Esses resultados estão de acordo com os resultados encontrados neste trabalho. Em todas as repetições, T1 e T2 apresentaram menor quantidade de conídios viáveis em comparação com o controle.…”
Section: Resultado E Discussãounclassified
“…Estes casos de hepatotoxicidade podem ser causados pelas kavalactonas por meio de três mecanismos: inibição do citocromo P450, redução da glutationa no rim, ou inibição da atividade da enzima ciclooxigenase (Clouatre, 2004). Muitos dos casos de hepatotoxicidade são relacionados ao consumo de produtos contendo extratos de kava preparados por métodos de extração com solventes (Jhoo et al, 2006). Assim, este trabalho mostrou a relevância do estudo das propriedades mutagênicas das plantas medicinais que, por serem consideradas "naturais" pela cultura popular, muitas vezes são utilizadas indiscriminadamente.…”
Section: Resultado E Discussãounclassified
“…Root and aereal parts of plants may exert different cytotoxic effects due to the active component contents and its distribution (Jhoo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%